From cantonments to townships: Lugard's influence upon British colonial urban governance in Africa. (2nd January 2019) - Home, Robert
ABSTRACT: The cantonment has been a neglected topic of planning history, yet is significant for urban landscapes and governance in both India and Africa. Drawing upon scholarship in critical comparative legal geography, path dependency and Foucault's genealogical method, the article explores the transfer of laws and regulations for urban governance by networks of knowledge and actors, tracing a line of descent from rules for cantonments in British India, through Lugard's Nigerian period, and his indirect rule policy to townships and local government ordinances. The influence of Lugard's Political Memoranda and Dual Mandate books is evidenced through the work of various senior officials moving between colonies, specifically South Africa, Kenya, and Northern Rhodesia.